2023
DOI: 10.35378/gujs.972909
|View full text |Cite
|
Sign up to set email alerts
|

The Determination of Presence of Listeria monocytogenes in Ground Meat Sold in Istanbul

Abstract: Among the 21 different species of the Listeria genus, Listeria monocytogenes is the most common and listeriosis agent in humans. The mortality rate of L. monocytogenes infection is higher than the other common foodborne pathogens such as Salmonella Enteritidis, Campylobacter and Vibrio species. In the current study, it is aimed to determine the presence of L. monocytogenes bacteria in minced meat samples sold in Istanbul province by using the culture method of the USDA-FSIS. In this study, 100 minced meat samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…Our findings are in agreement with data reported on antibiotic resistance of L. monocytogenes isolated from meat and meat products in other studies (Wang et al, 2013;Arslan and Baytur, 2019;Matle et al, 2019;Uluda g et al, 2023). Ampicillin or penicillin G in combination with an aminoglycoside such as gentamicin is a first choice for treating human listeriosis.…”
Section: Antibacterial Effect Of White Vinegarsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are in agreement with data reported on antibiotic resistance of L. monocytogenes isolated from meat and meat products in other studies (Wang et al, 2013;Arslan and Baytur, 2019;Matle et al, 2019;Uluda g et al, 2023). Ampicillin or penicillin G in combination with an aminoglycoside such as gentamicin is a first choice for treating human listeriosis.…”
Section: Antibacterial Effect Of White Vinegarsupporting
confidence: 93%
“…In our study, L. monocytogenes was detected in 9 (30%) out of 30 retail ground meat samples. L. monocytogenes was detected within the range of 12.4-41.9% in raw meat and meat products in recent studies in different regions of Türkiye and in various countries in the world (Wang et al, 2013;Arslan and Baytur, 2019;Matle et al, 2019;Uluda g et al, 2023). The results of these studies showed that the contamination rates of L. monocytogenes in raw meat samples were quite high.…”
Section: Detection Of L Monocytogenesmentioning
confidence: 93%
“…The 21st century is plagued by the emergence of multidrug-resistant bacteria such as foodborne pathogenic strains of Listeria and Shiga toxin-producing Escherichia coli (STEC) [1,2]. The major contributing factors to their antimicrobial resistance include the routine application of antimicrobials in domestic livestock for growth promotion, disease treatment, and prophylaxis [3].…”
Section: Introductionmentioning
confidence: 99%